1,3-Butadiene Production by Crotyl Alcohol Dehydration over Solid Acids and Catalyst Deactivation by Water Adsorption - OKAMOTO, Masaki; ICHIJO, Tatsuya; KIMURA, Nobuhiro; TSURUTA, Keisuke; YOSHIDA, Naohiro; SEGAWA, Atsushi (Journal of the Japan Petroleum Institute, 2020)
We studied the synthesis of 1,3-butadiene via the dehydration of crotyl alcohol (2-buten-1-ol) over solid acids. Crotyl alcohol conversion and butadiene selectivity were both 95 % or more over commercial silica–alumina catalysts. However, a sudden decrease in catalytic activity was observed during the reaction. On the basis of the fact that the deactivated catalyst was regenerated by drying at 150-200 °C, it was revealed that the main cause of the catalyst deactivation was the adsorption of water formed during the reaction and not the coke formation. An analysis of the deactivated catalyst indicated that, since the formation of Al–OH by the hydrolysis of the Al–O–Al bond increased the hydrophilicity of the catalyst surface, the adsorption of water on the catalyst surface was promoted, whereas that of crotyl alcohol was probably inhibited. Moreover, on the basis of the catalyst characterization, it was concluded that silica–alumina catalysts with few silanol groups, few alumina-rich zones, and a low Si/Al ratio were preferable.